Induction and Maintenance of Local Structural Durability for High‐Energy Nickel‐Rich Layered Oxides. Issue 6 (6th May 2022) - Ma, Quanxin; Wang, Yuqin; Lai, Fulin; Meng, Junxia; Dmytro, Sydorov; Zhou, Lingfei; Yang, Mengqian; Zhang, Qian; Zhong, Shengwen
Abstract: Nickel‐rich layered oxides are one of the most promising cathode candidates for next‐generation high‐energy‐density lithium‐ion batteries. However, due to similar ion radius between Li + and Ni 2+ (0.76 and 0.69 Å), the Li + /Ni 2+ mixing phenomenon seriously hinders the migration of Li + and increases kinetic barrier of Li + diffusion, resulting in limited rate capability. In this work, the introduction of Ce 4+ to effectively improve electrochemical properties of Ni‐rich cathode materials is proposed. The LiNi0.8 Co0.15 Al0.05 O2 (LNCA) is modified with an additional precursor oxidization process using an appropriate amount of (NH4 )2 Ce(NO3 )6 . The Ce(NO3 )6 2− easily obtains electrons and generates reduction reactions, while Ni(OH)2 is prone to electron loss and oxidation reaction. The participation of (NH4 )2 Ce(NO3 )6 can promote the oxidation of Ni 2+ to Ni 3+, thereby reducing the Li + /Ni 2+ mixing and increasing the structural stability of LNCA samples. Ce 4+ cation doping can impede Li + /Ni 2+ mixing of LNCA cathode materials upon the long‐term cycles. Both rate performance and long‐term cyclability of Li[Ni0.8 Co0.15 Al0.05 ]0.97 Ce0.03 O2 (LNCA‐Ce0.03) sample are significantly improved. Besides, a practical pouch cell based on the cathode presents sufficient gravimetric energy density (≈300 Wh kg −1 ) and cycling stability (capacity retention of 81.3% after 500 cycles at 1 C). Abstract : The charge density difference and corresponding 2D slices of Ce(NO3 )6 2− –Ni(OH)2, the electron localization function diagrams of the optimal configurations of LiNiO2 and Ce‐LiNiO2, and the long‐term cycling performance at 1.0 C for the LNCA/G and LNCA‐Ce0.03/G pouch cells are presented.